2020
DOI: 10.1093/toxsci/kfaa106
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Directs Stem Cell Fate by Imparting Notch Signaling Into the Extracellular Matrix Niche

Abstract: Abstract Compromise of skeletal muscle metabolism and composition may underlie the etiology of cardiovascular and metabolic disease risk from environmental arsenic exposures. We reported that arsenic impairs muscle maintenance and regeneration by inducing maladaptive mitochondrial phenotypes in muscle stem cells (MuSC), connective tissue fibroblasts (CTF), and myofibers. We also found that arsenic imparts a dysfunctional memory in the extracellular matrix (ECM) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Experimental studies support the findings of our study. Exposure to arsenic in vivo and in vitro caused impaired functions and regeneration capacity of the muscle [ 19 , 20 , 21 , 71 ]. Exposure to arsenic causes an impairment of muscle mitochondrial morphology and functions in mice [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies support the findings of our study. Exposure to arsenic in vivo and in vitro caused impaired functions and regeneration capacity of the muscle [ 19 , 20 , 21 , 71 ]. Exposure to arsenic causes an impairment of muscle mitochondrial morphology and functions in mice [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in skeletal muscle mass is also associated with pathogenic increases in the intramuscular fat (myosteatosis) [ 14 , 15 , 16 ], which leads to the promotion of IR [ 17 , 18 ]. Recently, experimental studies using animals and cultured cells have shown that arsenic affects the functions and regeneration of muscle [ 19 , 20 , 21 ]. However, less attention has been paid to the effects of arsenic exposure on the quantity and quality of the muscle in human studies.…”
Section: Introductionmentioning
confidence: 99%